Design and Technology of Liquisolid Compacts - Jomon N. Baby, Steffy B. Manjila, E.N. Bijin, Icey Constantine, K. Pramod, J. Valsalakumari (Journal of Applied Pharmaceutical Science, 2013)
During the emergence of a new drug it is very important to ensure its systemic bioavailability. Majority of the drugs in the developmental pipelines confronts with the problem of poor solubility; which will result in reduced dissolution rate there by hampering its bioavailability. Here comes the need of liquisolid technique which is a novel and promising approach to overcome these consequences. This technique utilizes the powder solution technology which is based upon the dissolution of the insoluble drug in the nonvolatile solvent and admixture of drug loaded solutions with appropriate carrier and coating materials to convert into acceptably flowing and compressible powders. The liquisolid technology can also be used both for the enhancement and the retardation of drug release by suitably altering the adjuvants. This aricle highlights the relevancy, formulation and designing of the liquisolid systems.
Keywords: Excipient ratio, Liquid load factor, Carrier material, Coating material, Bioavailability, Solubility.